Future career anxiety and indecision of hospitality students in UiTM Pulau Pinang branch amid COVID-19 pandemic / Fatin Nadhirah Zulfakar ... [et al.] - Zulfakar, Fatin Nadhirah; Mohamad Saber, Joesri; Ibrahim, Mohd Zoolfadli; Salim, Azlan; Abdul Ghani, Mastura; Lahap @ Wahab, Johanudin (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The outbreak of COVID-19 had been a significant concern to hospitality students that creates anxiety regarding their careers. The purpose of this study is to examine the influence of future career anxiety on indecision among students amid COVID-19. This study proposed a framework linking future career anxiety and indecision. A total of 170 undergraduate students from the Faculty of Hotel and Tourism Management, UiTM Pulau Pinang Branch, representing a response rate of 77.3%, participated in this study. The method used is the quantitative method, and the data for all the study variables were collected through online survey questionnaires. Multiple regression analyses were conducted to test the hypothesis. The empirical result of this study reveals a positive influence between future career anxiety and indecision among students amid COVID-19. The students experienced substantial career anxiety during the COVID-19 pandemic and reported being highly indecisive about choosing a career. The study's theoretical and practical implications and recommendations for future research were also discussed.